Transparansi Data Pembangunan Kesehatan Perspektif Open Government Data - Nurrahma, Mariam Rista Aulia (Universitas Airlangga, 2020)
Abstract The purpose of this study is to describe the disclosure of local government health development data in the perspective of public data disclosure. Open data that is interoperable with high accessibility and easy to access so that it can assist the government and the public in integrating planning, implementation, monitoring, evaluation, and control of development. This study used descriptive qualitative method. The data collection technique used was in-depth interview method. The informant determination technique uses a purposive technique where the selected informant is the party who is considered to know and understand the most. The result of the research is that the openness of local government health development has not been optimal. The data lacks a level of detail, is not updated, and is not published in an open format. Keywords: Open Government Data, transparency, local government Abstrak Tujuan penelitian adalah mendeskripsikan keterbukaan data pembangunan kesehatan pemerintah lokal dalam perspektif keterbukaan data publik. Open data yang memiliki sifat interoperabel dengan aksesibilitas yang tinggi dan mudah diakses sehingga dapat membantu pemerintah dan publik dalam memadukan perencanaan, pelaksanaan, pemantauan, evaluasi, serta pengendalian pembangunan. Penelitian ini menggunakan metode deskriptif kualitatif. Teknik pengumpulan data yang digunakan dengan metode wawancara mendalam. Teknik penentuan informan menggunakan teknik purposive dimana informan yang dipilih adalah pihak yang dianggap paling mengetahui dan memahami. Hasil penelitian adalah keterbukaan pembangunan kesehatan pemerintah lokal belum optimal. Data tidak memiliki tingkat detail, tidak update, dan tidak dipublikasikan dalam format terbuka. Kata kunci: open government data, transparansi, pemerintah lokal